SEQUESTRATION OF Pb2+AND Cd2+ IONS FROM AQUEOUS SOLUTIONS USING Rinorea dentata LEAF POWDER AS A LOW-COST ADSORBENT - Agwogie, Bright Aiyehirue; Jasper, Enebi; Soliu, Lanre Tijani; Okotcha, Evangeline Nwakaego; Onofuevure, Andrew Ogheneovo; Unoka, Edith Chinyere; Yakasai, Jamila Bashir; Efetobo, Oghenetega (FUDMA Journal of Sciences, 2026)
Rinorea dentata leaf powder (RDLP) was evaluated as a low-cost adsorbent to sequester Pb2+ and Cd2+ ions from aqueous solutions. Physicochemical analyses showed a pore volume estimate of 3.8 × 10⁻³ cm³/g, low moisture, ash, and volatile matter content. RDLP’s surface was confirmed as porous and irregular by scanning electron microscopy, while energy dispersive X-ray spectroscopy (EDX) identified carbon as the dominant element occurring with small amounts of oxygen and nitrogen. Optimal adsorption conditions of 10 mg/L initial metal ion concentration, pH 6, 80 min contact time, 0.6 g adsorbent dose, and 30 µm particle size were determined through batch adsorption experiments conducted at ambient temperature. The Langmuir isotherm model provided a better fit (R² = 0.980 for Pb²⁺ and 0.992 for Cd²⁺) than the Freundlich model, although both models reasonably described the adsorption behaviour, indicating favourable adsorption with predominantly monolayer coverage at lower concentrations, and the presence of surface heterogeneity as suggested by SEM/EDX and the Freundlich model. The pseudo-first order model provided the best fit to the experimental data (R² = 0.954 for Pb²⁺ and 0.972 for Cd²⁺), suggesting physical interactions; however, the intraparticle diffusion contributed to the rate-limiting step, particularly for Cd2+ ions. The thermodynamic studies revealed a low enthalpy change (ΔH=14.321 kJ/mol for Pb²⁺ and ΔH =15.026kJ/mol for Cd²⁺ ions, respectively), signifying that the adsorption process was endothermic and thermodynamically feasible with increasing spontaneity at higher temperatures. Overall, RDLP demonstrates strong potential as an inexpensive and effective adsorbent for heavy metal remediation in aqueous systems.